Methanolic crude extract of Litsea Monopetala leaves combats oxidative stress, clot formation, inflammation and stool frequency in animal model. - Sarder Arifuzzaman; Zubair Khalid Labu; Banani Das Ani; Samira Karim; Md Tarekur Rahman (PLoS ONE)
Introduction Litsea monopetala (LM) leaves are used in traditional medicine system in the South Asian region for treating ailments such as digestive issues, respiratory problems and skin disorders. In this study, we investigated the possible antioxidant, thrombolytic, analgesic and antidiarrheal properties of the methanolic extract of LM leaves. Method We assessed the antioxidant activity using DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging and total phenolic content tests, while thrombolytic activity was evaluated by clot lysis assays. The in-vivo analgesic and antidiarrheal activities were tested by two standard methods, e.g., acetic acid-induced and castor oil-induced animal model, respectively. Prior to in vivo and in vitro evaluation of the pharmacological activities phytochemical screening was also performed to estimate the bioactive compounds (e.g., phenol, carbohydrates, reducing sugars, tannins, alkaloids, flavonoids, saponins and steroids) present. Results Among the tested phytochemicals, our results reveal carbohydrates, alkaloids, flavonoids and tannins as the major phytocompounds present in the extract. Within the different solvent extractives, the methanolic extract exhibited DPPH free radical scavenging features with an IC50 of 8.99 µg/ml compared to ascorbic acid, an IC50 of 13.38 µg/ml. At 500 mg/kg dose, the extract produced 67.05% decrease in the frequency of acetic acid-induced writhing while diclofenac sodium showed decrease by 74.25%. The extract also significantly (P < 0.01) decreased the frequency of castor oil-induced diarrhea in compared to the standard drug of loperamide. Finally, the clot lysis assay with the methanolic extract demonstrated an increase in the thrombolytic activity by 40.79% compared to streptokinase, which increased by 69.52%. Conclusion Overall, this study shows promise that the methanolic crude extract of LM leaves may contribute to the alternative or additive strategy to modulate conditions of oxidative stress, thrombolytic, inflammation and diarrhea. Further comprehensive investigation is necessary to clarify the exact mechanisms of action and the phytochemical composition of LM leaves.